2008
DOI: 10.4049/jimmunol.181.9.6625
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Antibody Response against NeuGcGM3 Ganglioside Elicited in Non-Small Cell Lung Cancer Patients Immunized with an Anti-Idiotype Antibody

Abstract: 1E10 mAb is an anti-Id murine mAb (Ab2 mAb) specific for an Ab1 mAb that reacts with NeuGc-containing gangliosides, sulfatides, and Ags expressed in some human tumors. In preclinical studies, this Ab2 Ab was able to mimic NeuGc-containing gangliosides only in animals lacking expression of these Ags in normal tissues. In this study, we report on the immune responses elicited in 20 non-small cell lung cancer patients treated with 1 mg of aluminum hydroxide-precipitated 1E10 mAb. In the hyperimmune sera from 16 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(92 citation statements)
references
References 52 publications
3
89
0
Order By: Relevance
“…Our group has previously reported the induction of an antibody response against NeuGcGM3 ganglioside in patients with breast, melanoma, SCLC, and NSCLC treated with the racotumomab-alum vaccine (28,29,32,33). In the present study, we confirmed the immunogenicity of this anti-idiotype vaccine.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our group has previously reported the induction of an antibody response against NeuGcGM3 ganglioside in patients with breast, melanoma, SCLC, and NSCLC treated with the racotumomab-alum vaccine (28,29,32,33). In the present study, we confirmed the immunogenicity of this anti-idiotype vaccine.…”
Section: Discussionsupporting
confidence: 87%
“…The lytic capacity of patients' sera was tested by incubating the 1:5 diluted sera with 10 5 tumor cells in DMEM/F12 medium supplemented with 1% FBS in 5% CO 2 atmosphere at 37 C, for 3 hours (33,39,41). Cell death percent was determined by flow cytometry after the addition of propidium iodide (PI; Sigma-Aldrich) at a final concentration of 10 mg/mL.…”
Section: Induction Of Cell Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…[58][59][60][61]63 A positive correlation between the development of such antibodies and patient survival was found. 63 Despite the lack of direct cytotoxicity by P3 mAb, 66 the antibodies generated by the anti-idiotypic vaccine were able to directly kill GM3(Neu5Gc)-expressing cells. 91 Furthermore, these antibodies induced a 14F7-like type of cell death, including the formation of the membrane lesions on target cells, even at 4°C.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 80%
“…GM3(Neu5Gc) is a ganglioside whose expression has been detected in some human tumors, including breast and melanoma. 53,55,56 Several therapeutic strategies have been developed against this target, 14 e.g., vaccines (ganglioside-based 57 and antiidiotypic [58][59][60][61][62][63] ) and mAbs. 55 14F7 mAb is specific for this ganglioside and unable to bind its N-acetylated (Neu5Ac) counterpart.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%